STRATEGIES APPLIED IN SIMULTANEOUS INTERPRETING AT THE 2013 APEC SUMMIT CONFERENCE - Wiguna, Dewa Ketut Sudiarta (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 21 (2014): September 2014, 2014)
Interpreter has an important role in bridging communication of the people from different language and culture. Therefore, he or she should apply strategies of interpreting in rendering long and complicated utterances which is done simultaneously. It is interesting and challenging in analyzing simultaneous interpreting because it has a complexity in rendering the rendition at the same time as the speaker. The aim of this study is to analyze the strategies of simultaneous interpreting at press conference applied at the 2013 Asia Pacific Economic Cooperation Summit Conference. The methodology of this study is qualitative research through non-participative observation by observing the product of simultaneous interpreting involving the speaker, journalists and interpreter and recorded them by audio digital recorder. The audio recording data were transcribed into written texts. The relevant data were classified related to the strategies and it is analyzed through a descriptive analysis. There were ten strategies applied by the interpreter in simultaneous interpreting, i.e., reformulation, efficiency in reformulation, simplification, strategy applied if the interpreter made mistake, strategy applied if the speaker made mistake, avoids committing in rendering joke, anticipation, explanation, omission, and summarizing (addition).
Keywords: interpreting, simultaneous, conference, and strategy